Pembelajaran Organisasi—Peningkatan Berkelanjutan Bagi Iklim Keselamatan Pasien: Analisis Menggunakan PLS-SEM - Suryo Wibowo; Michael Christian; Sunarno Sunarno; Rima Melati; Susanty Dewi Winata (ARKESMAS [Arsip Kesehatan Masyarakat], 2022)
ABSTRACT The same awareness and perception of health professionals in hospitals regarding a patient-centered safetyclimate is very likely to be found to be non-uniform. Indeed, this will have an impact on organizational learning—continuous improvement, which is also linked to management support. Using these two aspects, this study intendsto investigate the determinants of organizational learning—continuous improvement. This is a quantitative studythat used a randomized survey of 48 health professionals working in hospitals throughout Indonesia. Data wascollected using a questionnaire as a research instrument, and the analysis tool in this study was structuralequation modeling—partial least squares with SmartPLS. The findings of this study support that safety climatehas a significant impact on organizational learning—continuous improvement (p = 0.007). This study's nextfinding explains that management support has a significant effect on organizational learning—continuousimprovement (p = 0.003). In this study, management support had no moderating effect (p = 0.127). According tothis study, 70.4 percent of organizations use safety climate and management support to measure organizationallearning and continuous improvement. Keywords: Safety Climate, Safety Management, Patient Safety, Organizational Learning, Health Professionals